2014
DOI: 10.1007/s00439-014-1499-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of the transthyretin gene in wild-type transthyretin amyloidosis (ATTRwt)

Abstract: Wild-type transthyretin amyloidosis (ATTRwt), typically diagnosed as congestive heart failure in elderly Caucasian men, features myocardial amyloid deposits of wild-type plasma protein transthyretin (TTR). ATTRwt is sporadic, its pathogenesis is poorly understood, and currently there are no biomarkers for diagnosis or prognosis. Genetic studies of variant-associated transthyretin amyloidosis (ATTRm) have suggested that non-coding TTR gene variants modulate disease. We hypothesized that cis-acting regulatory el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
16
2
Order By: Relevance
“…There was no difference in survival when stratified by AF type, paroxysmal (hazard ratio 1.04, P = 0.89) or long standing (hazard ratio 1.37, P = 0.29). We have recently reported that a TTR concentration of <180 mg/dL was associated with reduced survival in ATTRwt . Among patients with AF, we observed borderline significant survival differences with this threshold (hazard ratio 2.0, P = 0.059; Figure B ).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…There was no difference in survival when stratified by AF type, paroxysmal (hazard ratio 1.04, P = 0.89) or long standing (hazard ratio 1.37, P = 0.29). We have recently reported that a TTR concentration of <180 mg/dL was associated with reduced survival in ATTRwt . Among patients with AF, we observed borderline significant survival differences with this threshold (hazard ratio 2.0, P = 0.059; Figure B ).…”
Section: Resultsmentioning
confidence: 66%
“…We have recently reported that a TTR concentration of <180 mg/dL was associated with reduced survival in ATTRwt. 17,18 Among patients with AF, we observed borderline significant survival differences with this threshold (hazard ratio 2.0, P = 0.059; Figure 2B). The primary cause of death with heart failure which was noted in 22 of 39 (56%) of desceased patients with AF, and 8 of 10 (80%) of deceased patients without AF.…”
Section: Survivalmentioning
confidence: 89%
“…In addition to interindividual differences in common genetic variants of the transthyretin and TBG gene, differences in exposure to endocrine disrupting compounds (EDCs) may also contribute to the relatively large differences in overlap between abnormal TT4 and FT4 levels observed in our study. [24][25][26] There is a rapid increase in human exposure to EDCs, 27 and many EDCs have been shown to be potent competitive binders to thyroid hormone binding protein such as transthyretin and TBG. 28,29 To our knowledge, this is the first study that systematically investigated the feasibility of the use of TT4 as a marker of maternal thyroid function during the first half pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs as cardiomyopathy in elderly men with European ancestry, and TTR amyloid fibrils can be found in the hearts of the 25% of elderly individuals over 80 years of age [35]. A recent study provided suggestive evidences regarding the role of non-coding regulatory regions in wild-type TTR amyloidosis [36]. Together with these previous findings, our data suggest that TTR non-coding variation and its effect on transcription regulation are strong candidates as casual factors in the non-inherited form of TTR amyloidosis.…”
Section: Discussionmentioning
confidence: 99%